Using Technology for Foreign Language Learning: The Teacher’s Role - Nagy, Tünde (Central European Journal of Educational Research, 2021)
The spread of information technology has changed the role of language teachers considerably. Being a good educator and an expert in their field are not enough anymore, but teachers are expected to be modern, which means, to possess the ability to design interactive classes (often by using digital tools) and use teaching methods that engage students in a creative way. Today it is a general requirement for teachers to know their way around technology and to possess the know-how of implementing it in a way that fosters language learning. To this purpose teachers need to take into account all facets of technology use, including the advantages and disadvantages of technology-mediated tasks, their usefulness for language learning (e.g. if they are related to the topic of the lesson, are challenging enough for students), helpful resources for students, etc. Technology is regarded as a supplementary instrument to traditional teaching methods that can impact students’ motivation to learn in a positive way, provided it is used for activities that are in line with their needs and expectations. Task-based activities are considered to be especially useful in this regard, allowing students to practice their language skills in an authentic context and also develop creative thinking and problem solving abilities. Web 2.0 technologies (e.g. software programs for creating quizzes and polls, language learning websites, chat programs, wikis, etc.) offer a variety of valuable resources both for activities in the classroom and for practice at home.